Myocardial Perfusion Reserve Index in Children With Kawasaki Disease. Issue 1 (12th December 2017) - Friesen, Richard M.; Schäfer, Michal; Jone, Pei‐Ni; Appiawiah, Nana; Vargas, Daniel; Fonseca, Brian; DiMaria, Michael V.; Truong, Uyen; Malone, LaDonna; Browne, Lorna P.
Abstract : Background: Coronary artery lesions in patients with Kawasaki disease (KD) can impair myocardial perfusion, yet evaluation of perfusion defects by cardiac magnetic resonance (MR) in children is often qualitative. Purpose: In this study we aimed to use a quantitative method of myocardial perfusion using stress cardiac MR‐derived myocardial perfusion reserve index (MPRI) in children with KD and compare MPRI with ventricular mechanical performance evaluated by cardiac MR strain analysis. Study Type: This study was a retrospective review. Subjects: Twenty‐one children with a diagnosis of KD who underwent stress perfusion cardiac MR were compared with nine controls. Field Strength/Sequence: First‐pass perfusion imaging using a T1 ‐weighted gradient echo sequence was performed at rest and stress after administration of adenosine with 1.5T or 3T magnets. Assessment: The MPRI was calculated as the ratio of maximum slope of myocardial enhancement during stress compared to rest and was evaluated with the American Heart Association 17 segment model. Statistical Tests: Demographic and clinical characteristics among KD patients and controls were compared using Student's t ‐test for normally distributed continuous variables, Wilcoxon‐rank sum test for nonnormally distributed variables, and χ 2 for categorical variables. Results: There was a significant decrease in MPRI in Segment 7 (1.53 vs. 2.23, P = 0.0058) in KD patients compared with controls. The reduction in MPRI in Segment 12 approached statistical significance (1.58 vs. 2.31, P = 0.0636). Three patients who underwent serial studies had decreased MPRI longitudinally. No differences were seen in circumferential or radial strain. Data Conclusion: MPRI shows impaired myocardial perfusion in patients with KD. MPRI can change over time, suggestive of progressive coronary artery changes, which may precede fibrosis and mechanical decline. MPRI can assess segmental and global perfusion defects in patients with KD and should be a part of routine cardiac MR evaluation in KD. Level of Evidence : 3 Technical Efficacy Stage 3 J. Magn. Reson. Imaging 2017.